Case report: Drug reaction with eosinophilia and systemic symptoms (DRESS)-induced hemophagocytic disorder - Pope, Eliza I.; Au, Hosanna; Levy, Deborah M.; Verstegen, Ruud H. J. (Frontiers in Pharmacology, 2022)
Hemophagocytic disorders are severe and life-threatening conditions that can be genetic in origin [i.e., primary hemophagocytic lymphohistiocytosis (HLH)] or result from infections (i.e., secondary hemophagocytic lymphohistiocytosis), rheumatologic disease [i.e., macrophage activation syndrome (MAS)], and less frequently immunodeficiency or metabolic disease. Although rare, drug-induced hemophagocytosis needs to be considered in the work-up as it requires specific management strategies. Most drug-induced hemophagocytic disorders are related to Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS). We present the case of a 7-year-old girl who initially presented with fever, maculopapular rash, and unilateral lymphadenopathy, who went on to develop hemophagocytosis secondary to DRESS caused by prolonged combination treatment with amoxicillin/clavulanic acid and trimethoprim/sulfamethoxazole. This case illustrates the importance of considering adverse drug reactions in the evaluations of patients with a hemophagocytic process.